PENERAPAN PENDIDIKAN AKHLAK KELAS IV SEKOLAH DASAR PERSATUAN UMAT ISLAM (PUI) HAURGEULIS INDRAMAYU - Sami’in, Sami’in; Moch. Hasyim Fanirin (JOEL: Journal of Educational and Language Research, 2022)
Moral learning is very important because later it will shape the attitude, behavior and identity of a child because the formation of high morals is the main goal in Islamic education. Morals are closely related to the mindset, attitude of life and human behavior. Bad morals have the potential to trigger negative behavior. If the character of a child is bad, it will give birth to various behaviors whose impact can be detrimental to himself and others. Good morals can lead to positive values so that they can form a Muslim personality who is obedient to Allah. The purpose of this study was to find out how the application of morality lessons in Islamic Community Education Elementary School (PUI) Haurgeulis Indramayu. This study uses descriptive qualitative research, in qualitative research data collection is obtained by means of interviews, documentation, and observation. The results showed that: The application of moral learning in SD PUI Haurgeulis uses lesson plans in accordance with the 2013 curriculum. In the implementation of learning, teachers use the lecture method, which is still very dominant in the learning process carried out. Likewise with the use of media, moral teachers adjust the media according to the material to be studied and for practice every day the faith teacher holds a congregational prayer program at noon, always says greetings when meeting with teachers, parents, and other fellow students.